Lymphoepithelial cyst in the palatoglossus arch Quiste linfoepitelial en el arco palatogloso - Evanice Maria Marçal Vieira; Vinícius Canavarros Palma; Tereza Aparecida Delle Vedove Semenoff; Andreza Maria Fábio Aranha; Flares Baratto-Filho; Álvaro Henrique Borges (Editorial Ciencias Médicas, 2012)
The objective of this study was to describe a case of a lymphoepithelial cyst in the palatoglossus arch. A 16-years-old black man said that he was observed a lesion in his mouth. On the physical exam, a pedicled, consistent, smooth surface 1.5 x 1 cm lesion, similar in color to the adjacent mucosa, was found. The lesion was surgically removed and the microscopic exam showed mucosal fragments with pedicled lesion; the cystic cavity sometimes lined with pseudostratified cylindrical epithelium and others with stratified squamous flat interface of the epithelium. Around the cyst, a well-delimited mass of lymphoid tissue, presenting lymphoid follicles, was also seen. Lymphoepithelial cyst has clinical characteristics similar to those of others lesions that occur in the oral cavity. The diagnosis should be based on conservative biopsy, with total removal of lesion. El objetivo de este estudio fue describir un caso clínico de quiste linfoepitelial en el arco palatoglosso. Paciente de 16 años de edad, sexo masculino, raza negra, que durante la anamnesis relató que observó una lesión en la boca. Al examen físico se observó una lesión pediculada, de consistencia firme, superficie lisa, de 1,5 x 1,0 cm de tamaño, con color similar al de la mucosa adyacente. La lesión fue removida quirúrgicamente y el examen microscópico mostró fragmentos de mucosa con lesión pediculada, la cavidad del quiste a veces revestida por epitelio cilíndrico pseudoestratificado y otras veces por la interfase plana del epitelio escamosa estratificado. Alrededor del quiste, una masa bien delimitada de tejido linfoide con presencia de folículos linfoides. El quiste linfoepitelial tiene las mismas características clínicas de otras lesiones que ocurren en la cavidad oral, el diagnóstico debe ser realizado por biopsia, de manera conservadora, con eliminación total de la lesión.